2012
DOI: 10.1038/emboj.2012.93
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-2 is an initiator caspase responsible for pore-forming toxin-mediated apoptosis

Abstract: Bacterial pathogens modulate host cell apoptosis to establish a successful infection. Pore-forming toxins (PFTs) secreted by pathogenic bacteria are major virulence factors and have been shown to induce various forms of cell death in infected cells. Here we demonstrate that the highly conserved caspase-2 is required for PFT-mediated apoptosis. Despite being the second mammalian caspase to be identified, the role of caspase-2 during apoptosis remains enigmatic. We show that caspase-2 functions as an initiator c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 48 publications
3
59
0
Order By: Relevance
“…Previous studies have shown that high extracellular K ϩ levels prevented PFT-induced p38 MAPK activation and cell death (22,24,31). We observed that beta-toxin did not lead to cell death or the activation of p38 MAPK in THP-1 cells in K ϩ -high medium, which indicated that K ϩ efflux through the toxin pore activates the p38 MAPK defense response.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have shown that high extracellular K ϩ levels prevented PFT-induced p38 MAPK activation and cell death (22,24,31). We observed that beta-toxin did not lead to cell death or the activation of p38 MAPK in THP-1 cells in K ϩ -high medium, which indicated that K ϩ efflux through the toxin pore activates the p38 MAPK defense response.…”
Section: Discussionsupporting
confidence: 51%
“…PFTs can also trigger apoptosis, which in the case of S. aureus alpha-toxin and aerolysin is dependent upon caspase-2. Preventing the PFT-associated efflux of potassium inactivated caspase-2, and inhibition of caspase-2 inhibited PFT-induced apoptosis (318). Potassium efflux was also found to be required for PFT-induced autophagy (311,319) and to mediate p38 MAPK activation by S. aureus alpha-toxin, Vibrio cholerae cytolysin (VCC), SLO, and E. coli hemolysin A (HlyA) (320).…”
Section: Potassium Efflux-dependent Defenses Including Inflammasome mentioning
confidence: 99%
“…Other alternative caspase-2 activation mechanisms have been described, including caspase-2 dimerization and subsequent autoproteolysis, which is induced by K + efflux in response to bacterial pore-forming toxins (Imre et al, 2012) or heat-shock-triggered protein aggregation (Tu et al, 2006). Furthermore, alternative mRNA splicing (Wang et al, 1994), post-translational modifications, including N-terminal acetylation (Yi et al, 2011) and phosphorylation, appear to impact on and fine-tune these activating events (see poster).…”
Section: Modes Of Activationmentioning
confidence: 99%
“…Caspase-2-deficient murine macrophages are protected from Salmonella-induced cell death and show decreased processing of caspase-1, a major driver of inflammation upon infection (Jesenberger et al, 2000). Similarly, cells lacking caspase-2 are also protected from cell death induced by Staphylococcus aureus a-toxin, but the underlying mechanisms that are responsible for escape from cell death have not yet been defined (Imre et al, 2012).…”
Section: Modes Of Activationmentioning
confidence: 99%